Macrophages and Extracellular Matrix in Breast Cancer: Partners in Crime or Protective Allies? - Deligne, Claire; Midwood, Kim S. (Frontiers in Oncology, 2021)
Solid cancers such as breast tumors comprise a collection of tumor, stromal and immune cells, embedded within a network of tumor-specific extracellular matrix. This matrix is associated with tumor aggression, treatment failure, chemo- and radio-resistance, poor survival and metastasis. Recent data report an immunomodulatory role for the matrix in cancer, via the creation of niches that control the migration, localization, phenotype and function of tumor-infiltrating immune cells, ultimately contributing to escape of immune surveillance. Macrophages are crucial components of the immune infiltrate in tumors; they are associated with a poor prognosis in breast cancer and contribute to shaping the anti-tumor immune response. We and others have described how matrix molecules commonly upregulated within the tumor stroma, such as tenascin-C, fibronectin and collagen, exert a complex influence over macrophage behavior, for example restricting or enhancing their infiltration into the tumor, and driving their polarization towards or away from a pro-tumoral phenotype, and how in turn macrophages can modify matrix production in the tumor to favor tumor growth and metastasis. Targeting specific domains of matrix molecules to reinstate an efficient anti-tumor immune response, and effectively control tumor growth and spread, is emerging as a promising field offering a new angle for cancer therapy. Here, we review current knowledge on the interactions between tumor-associated macrophages and matrix molecules that occur within the tumor microenvironment of breast cancer, and discuss how these pathways can be targeted for new immunotherapies for hard to treat, desmoplastic tumors.